3D Imaging Insights into Forests and Coral Reefs. (January 2020) - Calders, Kim; Phinn, Stuart; Ferrari, Renata; Leon, Javier; Armston, John; Asner, Gregory P.; Disney, Mathias
Abstract : Forests and coral reefs are structurally complex ecosystems threatened by climate change. In situ 3D imaging measurements provide unprecedented, quantitative, and detailed structural information that allows testing of hypotheses relating form to function. This affords new insights into both individual organisms and their relationship to their surroundings and neighbours.